Analisis Kesalahan Basic Error Siswa dengan Menggunakan Scaffolding Pada Materi Eksponensial - Talib, Ahmad; Dassa, Awi; Sibian, Miske Elsy (Issues in Mathematics Education (IMED), 2024)
This study aims to analyze the types of basic errors made by students and describe the appropriate form of scaffolding to assist students in solving exponential problems correctly. This type of research is descriptive qualitative. There are 2 research subjects, those are SMAN 21 Makassar students who were selected based on the results of a diagnostic test with the highest number of basic error indicators (T2 and T1). Data collection techniques used in this study were tests and interviews. The results showed that: (1) Students experienced basic errors in the form of; do not understand the basic concepts of integers; do not understand the basic concept of power numbers; do not understand the concept of performing algebraic operations; and do not understand the exponential rule. (2) The forms of scaffolding given to students are environmental provisions, explaining, reviewing and restructuring, and developing contextual thinking. (3) Based on the results of the final test after giving scaffolding, it was able to minimize the basic errors made by students on exponential questions.